2019
DOI: 10.6061/clinics/2019/e789
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain in the elderly population: a systematic review

Abstract: The aim of this study was to estimate the prevalence of low-back pain (LBP) and to identify the level of functional disability in elderly individuals in different populations. From January 1985 to October 2018, a search was performed using the following databases: Embase, LILACS, SciELO, Scopus, Medline, and the Web of Science. The descriptors were low-back pain, back pain, lower-back pain, prevalence, and elderly in Portuguese and English. Two independent reviewers conducted a search for studies and evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 68 publications
3
75
0
9
Order By: Relevance
“…Several cross-sectional and longitudinal studies conducted in European countries have also provided very similar results, indicating a strong association between low back pain and HR-QoL [ 7 , 117 , 118 ]. Finally, a recent systematic reviews of 35 research paper published from 1985 to 2018 with a total sample of 135,059 older adults aged between 60 and 102 years confirmed a high prevalence of low back pain in older adults and functional disability that affects quality of life and factors important for independence [ 119 ]. It is important to note that this systematic review found a significant absence of studies among older Latino and African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional and longitudinal studies conducted in European countries have also provided very similar results, indicating a strong association between low back pain and HR-QoL [ 7 , 117 , 118 ]. Finally, a recent systematic reviews of 35 research paper published from 1985 to 2018 with a total sample of 135,059 older adults aged between 60 and 102 years confirmed a high prevalence of low back pain in older adults and functional disability that affects quality of life and factors important for independence [ 119 ]. It is important to note that this systematic review found a significant absence of studies among older Latino and African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [ 10 ], with data from the international literature on the prevalence of LBP in the older adult population (in developing or developed countries), indicates a high prevalence of LBP among older people, ranging from 21.7 to 75%. In the first nationwide meta-analysis that investigated the prevalence of LBP in older people in Brazil, Leopoldino et al [ 11 ] provided moderate-quality evidence that the punctual prevalence of LBP in older Brazilians was 25.0% (95% CI: 18.0–32.0%).…”
Section: Introductionmentioning
confidence: 99%
“…In the French portion of the World Mental Health Survey, the chronic back pain prevalence was reported 21.3% [30]. Another study reported the prevalence of LBP ranged from 21% to 75% in elderlies [31]. A study showed that 70-85% of the population will have an episode of LBP at some point and 90% of them will experience more than one episode [32].…”
Section: Discussionmentioning
confidence: 99%